Caracterización del Sistema de Tenencia y Perfil Hematológico - Bioquímico del Cerdo Criollo Ecuatoriano en la Provincia de Cotopaxi - Quimbita Cadena Elizabeth Catherine (2018)
The Creole pig is an omnivore animal easy to breed and prolific that has good rusticity adapting quickly to different climates and environments. The research was carried out with the aim of characterizing the land tenure system and the hematologic-biochemical profile of the Ecuadorian Creole Pig in Cotopaxi Province, Latacunga, Salcedo, Pujili, and Saquisili Cantons. One-hundred producers were surveyed to carry out the land tenure system analysis; the questionnaire analyzed among other aspects, the owners' general characteristics, history of the exploitation, the human resources, information regarding the unit of production, reproduction, and sanitary management. A population of 30 Creole pigs were used to carry out the hematologic-biochemical profile study, blood samples were taken to establish the hematologic and biochemical reference parameters, and the sex factor was considered as well. The descriptive statistic was developed in Excel, and on the Infostad program analysis of variance and Tukey test were carried out to the data analysis. The majority of the producers are female; its rusticity gives the dedication in the breeding of the Creole pig. The decrease considerably of the effects of the race is due to the indiscriminate mating. In the hematological profile, the variables of hematocrit, hemoglobin, erythrocytes show significant differences (P ≤ 0.05) according to favorable sex in males. However, VGM, MCH, CGMH, and platelets do not present significant differences. In the leukogram analysis, most of the variables do not show significant differences, only in the basophils found significant differences in females. Similarly, in the biochemical profile, most of the variables do not show significant differences except for potassium between females and males, favorable to males.